Female Epispadiasis: A Case report - Bhat, N; Wani, I (Journal of Nepal Paediatric Society, 2011)
Isolated female epispadias without exstrophy is rare to see. It is often overlooked cause of incontinence in a female child. A case of isolated female epispadias without exstrophy in an 11-year-old girl who presented with primary urinary incontinence since birth is reported. She had never had a genitalia examination done by any treating clinician. On examination, she had a bifid clitoris and ill developed labia minora. Voiding cystourethrogram showed small sized bladder with no reflux. Bladder neck reconstruction was done transvesically, with tubularisation of urethra. The case report reflects the importance of physical examination in primary incontinence which can make an early diagnosis and treatment and prevent stigmata of incontinence. DOI: http://dx.doi.org/10.3126/jnps.v31i3.4415 J Nep Paedtr Soc 2011;31(3): 244-246